Seed morphological studies of silene L., from Turkey - (:unkn) unknown (My University, 1998)
The genus Silene L., (Caryophyllaceae) from Turkey have been studied for their seed morphology. A total of 19 species of which 3 are endemic belonging to 12 sections were studied. The seeds show variation in their morphology. The seed morphology as studied show section specific observations.